How can African agriculture adapt to climate change: Assessing Household Vulnerability to Climate Change: The Case of Farmers in the Nile Basin of Ethiopia - Deressa, Temesgen T.; Hassan, Rashid; Ringler, Claudia (International Food Policy Research Institute, 2011)
Ethiopia remains one of the least-developed countries in the world: 50 percent of the population lives in abject poverty, and average life expectancy is only 43 years. Agriculture-the main sector of the Ethiopian economy-employs about 80 percent of the population and is dominated by small-scale, mixed crop and livestock production with very low productivity, which can be attributed to obsolete farming techniques; soil degradation caused by overgrazing and deforestation; poor complementary services, such as extension, credit, markets, and infrastructure; and frequent droughts and floods.